Competency of Adult Learners in Learning: Application of the Iceberg Competency Model. (24th August 2015) - Salleh, Kahirol Mohd; Khalid, Nur Hidayah; Sulaiman, Nor Lisa; Mohamad, Mimi Mohaffyza; Sern, Lai Chee
Abstract: Adult learning is a part of continuous learning concept that takes place for a lifetime. It encompasses several programmes for the enhancement of compentecy consist of knowledge, skills, and abilities. This research paper is published for the purpose of analysing the competency level of adult learners by applying the Iceberg competency model. The research focused on several aspects including learning requirement, application and strategy. Furthermore, it also attempted to identify the competency level together with learning requirement, application and strategy. For sampling technique, probability sampling with simple random sampling was employed. Research samples were 133 adult learners who are undergraduates at Universiti Tun Hussein Onn Malaysia (UTHM). Mean score, standard deviation and hierachical arrangement were used for reporting descriptive data. Results show that the learners' learning requirements are high. Likewise, analysis of their competency level also shows high scores for the interpersonal skill and knowledge domains. Overall analysis of the competency level of the adult learners shows the highest level of agreement for attitude and value domains. The results also show that the competency level of the learners is high even though the competency level can change from time to time. Therefore, teachers need to establish a system to evaluate the competency of adult learners. The system will serve as a benchmark in monitoring their competency.